The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3947/ic.2022.0061
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain and Metabolic Syndrome in Human Immunodeficiency Virus Patients

Abstract: While human immunodeficiency virus (HIV)-associated wasting has declined with significant advances in antiretroviral therapy (ART), weight gain and metabolic syndrome (MetS) are now becoming a problem for people living with HIV (PLWH) worldwide. The development of a new and more effective ART regimen has increased viral suppression and improved immunologic function recovery, leading to the extension of the lifespan of PLWH. It has recently been reported as one of the significant factors associated with weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…This finding is concurrent with those of studies conducted in the southern United States 33 and South Korea. 34 This could be explained by the baseline risk of MetS that the patient might have due to higher baseline weight and the associated risk of obesity, which can later be exacerbated by weight gain after treatment with ART.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is concurrent with those of studies conducted in the southern United States 33 and South Korea. 34 This could be explained by the baseline risk of MetS that the patient might have due to higher baseline weight and the associated risk of obesity, which can later be exacerbated by weight gain after treatment with ART.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude in this study is lower than the cohort study done in USA and Canada that showed nearly 30% of HIV patients had developed overweight/obesity during the follow up period. 24 This might be owing to HIV treatment complications and drug side effects in ART patients. Furthermore, it might be explained by the difference in the sample size and socio-demographic and economic variables.…”
Section: Discussionmentioning
confidence: 99%
“… 28 However, it is not supported by the cohort study done in USA and Canada that stated that women with HIV experience a significantly greater increase in BMI following ART initiation than men. 24 The possible explanation for the discrepancy might be difference of the population, socio economic status and ART drug type. Similarly, this finding is also not in line with other studies done so far in Zimbabwe, Botswana, Uganda and Jima 17 , 25 , 31 , 32 which showed that females were more likely to be overweigh/obesity as compared to male.…”
Section: Discussionmentioning
confidence: 99%
“…208 Before the ART era, people with AIDS had high levels of free fatty acids and plasma triglycerides, 209 in contrast to PLWH who did not have AIDS. 210,211 Particularly, the use of PIs was associated with increases in plasma total cholesterol and triglycerides in the Swiss HIV Cohort Study. 212,213 The occurrence of dyslipidemia in ART-adherent PLWH highlighted the need for lipid The schematic depicts the initiation of HIV type 1 (HIV-1) infection in T cells, which triggers and sustains elevated renin expression to facilitate its replication within the cell.…”
Section: Metabolic Changesmentioning
confidence: 99%